Chemical composition of the essential oil of the leaves of Hedyosmum luteynii Todzia (Chloranthaceae) - Torres Rodríguez, Silvia Hipatia (2018)
In this work, essential oil of Hedyosmum luteynii is characterize from samples collected in the Jacarón natural forest, Colta, Chimborazo, Ecuador. The essential oil was extracted by hydrodistillation; analysis of the composition was carried out by gas chromatograph, coupled to a mass spectrometer; identification of the components was made by comparing their mass spectra and the Kováts indexes reported in the literature. Twenty-eight compounds were identified, 98.62% of the total components. Natural hydrocarbon monoterpenes were the highger (83.21%). The most abundant components were: α-phellandrene (32.72%), α-pinene (13.20%), (Z)-β-ocimene (10.99%), silvestrene (6.51%), bicyclogermacrene (5.05%), 1.8-cineol (4.95%), (E)-β-ocimene (3.88%) and germacrene D (3.20%). For first time, silvestrene is reported as an important component of essential oil in one of the species of the genus Hedyosmum. This result is a important difference in the chemical composition of the essential oil of H. luteynii respect to other species of Hedyosmum.